PENERAPAN MEDIA PEMBELAJARAN CAMTASIA STUDIO UNTUK MENINGKATKAN EFEKTIFITAS BELAJAR SISWA KELAS XI IPA SMA NEGERI 11 MEDAN - SRI MINARTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The purpose of this study was to create learning media using the Camtasia Studio application on the subject matter of the Food Digestive System in CD form and to determine the level of effectiveness of student learning with the existence of learning media. The media trial was conducted at SMA Negeri 11 Medan with 74 students in two classes as respondents. The data collection tool used was in the form of observation sheets of student activities and evaluation of the media given to students, teachers and students as well as multiple choice questions. Learning media is made using the main software Camtasia Studio and other supporting software such as Format Factory and Youtube. The feasibility test of learning media according to learning media experts (students and teachers) obtained an average percentage of 75.96%, and the results of a questionnaire on students' perceptions of the media obtained an average percentage of 76.32% and 81.21%. The results of the data analysis showed that the level of students' mastery of the use of instructional media was 78.38% and 78.11%. In class XI IPA 1 there were 31 students who completed (83.78%) of 37 students and in class XI IPA 2 there were 33 students (89.19%) who completed from 37 students, classically learning completeness had been fulfilled. Achievement of specific learning objectives (TPK) for both classes is 100%, and from the overall observation results are good. From this study it can be concluded that computer-based learning media with the Camtasia Studio application on the subject matter of the Food Digestive System in CD form for students of class XI IPA 1 and 2 at SMA Negeri 11 Medan in the 2012/2013 Academic Year is appropriate to be used as a learning medium and is able to improve student learning activities. ABSTRAKTujuan penelitian ini untuk membuat media pembelajaran dengan menggunakan aplikasi Camtasia Studio pada materi pokok Sistem Pencernaan Makanan dalam bentuk CD dan mengetahui tingkat efektifitas belajar siswa dengan adanya media pembelajaran. Uji coba media dilakukan di SMA Negeri 11 Medan dengan jumlah responden 74 siswa dalam dua kelas. Alat pengumpul data yang digunakan berupa lembar observasi aktivitas siswa dan evaluasi media yang diberikan kepada siswa, guru dan mahasiswa serta soal bentuk pilihan berganda. Media pembelajaran dibuat dengan menggunakan software utama Camtasia Studio dan software pendukung lain seperti Format Factory dan Youtube. Uji kelayakan media pembelajaran menurut ahli media pembelajaran (mahasiswa dan guru) memperoleh persentasi rata-rata sebesar 75,96%, dan hasil angket persepsi siswa terhadap media diperoleh persentase rata-rata sebesar 76,32% dan 81,21%. Hasil analisa data diperoleh bahwa tingkat penguasaan siswa terhadap penggunaan media pembelajaran adalah 78,38% dan 78,11%. Di kelas XI IPA 1 terdapat 31 siswa yang tuntas (83,78%) dari 37 siswa dan di kelas XI IPA 2 terdapat 33 siswa (89,19%) yang tuntas dari 37 siswa, secara klasikal ketuntasan belajar telah terpenuhi. Ketercapaian tujuan pembelajaran khusus (TPK) untuk kedua kelas adalah 100%, dan dari hasil observasi secara keseluruhan adalah baik. Dari penelitian ini dapat disimpulkan bahwa media pembelajaran berbasis komputer dengan aplikasi Camtasia Studio pada materi pokok Sistem Pencernaan Makanan dalam bentuk CD untuk siswa kelas XI IPA 1 dan 2 di SMA Negeri 11 Medan Tahun Pembelajaran 2012/2013 layak untuk digunakan sebagai media pembelajaran dan mampu meningkatkan aktivitas belajar siswa.